Beach Area Changes and Resilience of the Eastern Coasts Before and After Typhoon Goni - Tae-Soon Kang; Ho-Jun Yoo; Ki-Hyun Kim (한국해양공학회지, 2024)
Due to climate change, waves have become increasingly stronger, making the analysis of beach changes before and after typhoons crucial for addressing beach erosion. This study utilized low-cost, high-efficiency video monitoring to analyze beach changes at 14 locations along Korea's east coast before and after typhoon impacts. Shorelines were extracted from 180 s average orthoimages using the Pixel Intensity Moving Average Extraction technique, and beach areas were calculated. The study focused on the recovery period following typhoon-induced erosion. During Typhoon Goni (2015), erosion reached up to 38% at Bongpo Beach, with a maximum affected area of 7,741 m2 at Goraebul Beach. Post-typhoon recovery exceeded 89%, with most beaches returning to pre-typhoon conditions. The erosion period averaged 7 d, while recovery took approximately 27 d. Erosion was significantly influenced by natural forces such as waves, tides, and wind. The erosion period showed minimal correlation with wave energy, whereas the recovery period exhibited some correlation. Further long-term analysis, incorporating additional wave data and typhoon impact periods, is needed. Future research will aim to collect extensive typhoon data to systematically analyze erosion and recovery cycles in relation to external forces.